"Men, Women, and Children Starving": Archaeology of the Donner Family Camp. Issue 3 (20th July 2010) - Dixon, Kelly J.; Novak, Shannon A.; Robbins, Gwen; Schablitsky, Julie M.; Scott, G. Richard; Tasa, Guy L.
Abstract : In spring of 1846, the George and Jacob Donner families and some 80 traveling companions began their overland trek to California. When the party ascended the Sierra Nevada in late October, a snowstorm forced the group to bivouac. At this point, the train became separated into two contingents; the larger party camped near Donner Lake and the smaller group—including the Donner families—settled at Alder Creek. Though written accounts from the Lake site imply many resorted to cannibalism, no such records exist for Alder Creek. Here we present archaeological findings that support identification of the Alder Creek camp. We triangulate between historical context, archaeological traces of the camp, and osteological remains to examine the human condition amid the backdrops of starvation and cannibalism. A stepped analytical approach was developed to examine the site's fragmentary bone assemblage ( n = 16, 204). Macroscopic and histological analyses indicate that the emigrants consumed domestic cattle and horse and procured wild game, including deer, rabbit, and rodent. Bladed tools were used to extensively process animal tissue. Moreover, bone was being reduced to small fragments; pot polish indicates these fragments were boiled to extract grease. It remains inconclusive, however, whether such processing, or the assemblage, includes human tissue.